DAMPAK PENERAPAN PSAK NO. 50 DAN 55 (REVISI 2006) TERHADAP FORWARD EARNINGS RESPONSE COEFFICIENT DAN RELEVANSI NILAI DARI DERIVATIF KEUANGAN: (STUDI EMPIRIS PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Oktavia, Oktavia; Siregar, Sylvia Veronica N.P.; Djakman, Chaerul D. (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to investigate the impact of Indonesian SFAS No. 50 and 55 (revised 2006) on the stock market’s ability to predict firms’ future earnings, which we refer to as stock price informativeness. Our proxy for the stock price informativeness is the forward earnings response coefficient, FERC. This study also investigated whether there is an increase in value-relevance of derivative financial instruments after the implementation of SFAS No. 50 and 55 (revised 2006) in Indonesia. This study found that: (1) the implementation of SFAS No. 50 and 55 (revised 2006) in financial firms which use derivative financial instruments, can increase the ERC but not increase the FERC, and; (2) After the implementation of SFAS No. 50 and 55 (revised 2006), the fair value of derivative financial instruments has significantly positive impact to the market value of equity. These findings suggest that the implementation of Indonesia SFAS No. 50 and 55 (revised 2006) has increased the transparency of derivative financial instrument.